Effects of cold press operating conditions on vegetable oil fatty acid profiles. Issue 10 (8th August 2016) - Zhao, Xianhui; Wei, Lin; Julson, James
ABSTRACT: Although most of jet fuels are currently made from petroleum, nonfood oilseeds such as flax and canola seeds may be an alternative for renewable jet fuel production in the near future. Vegetable oils produced from those oilseeds can be upgraded to liquid hydrocarbons to produce renewable jet fuels. The production efficiency and cost are heavily relied on the vegetable oil fatty acid profile (FAP). Previous research indicated that vegetable oil FAP is affected by oilseed species and oil extraction conditions. Cold press oil extractions from flax and canola seeds were conducted. The effect of the frequency controlling the screw rotating speed on the oil extraction efficiency and quality was discussed. Characterization of the vegetable oils produced, including density, pH value, viscosity, moisture, element component, heating value and FAP, was carried out. The residual oil contents left in the cold press meals were also determined. The results show that the oil extraction efficiency of oilseeds increased when the frequency decreased. For flax and canola seeds, their highest oil extraction efficiency was the same (81.0%), which was both obtained at 15 Hz. The cold press frequency had a minor influence on the FAPs of flax oils. However, the FAPs of canola oils produced at 15 Hz were different from those produced at 20 Hz and 25 Hz to some extent. The main fatty acid in flax and canola oils was linolenic acid and erucic acid, respectively.